2007
DOI: 10.1007/s10508-007-9271-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Ability and Prenatal Androgens: Meta-Analyses of Congenital Adrenal Hyperplasia and Digit Ratio (2D:4D) Studies

Abstract: Hormonal manipulations indicate that early androgens organize sex differences in spatial ability in animal models. In humans, spatial ability is also sexually dimorphic, and information about the effects of prenatal androgens on spatial ability can be obtained from studies of congenital adrenal hyperplasia (CAH) and the ratio of the second and fourth finger lengths (2D:4D). CAH is a condition characterized by prenatal overproduction of adrenal androgens, and several lines of evidence suggest that 2D:4D reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
146
3
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(154 citation statements)
references
References 71 publications
1
146
3
4
Order By: Relevance
“…With regard to the link between biological sex and abilities ( Figure A2 in the supplemental materials), also mediated by an effect on brain functioning and development, findings such as sex differences in white-gray matter ratios are promising but have not been causally linked to male advantage in three-dimensional mental rotation, thought to underlie male superiority in advanced mathematics. Similarly, the relationship between testosterone and spatial abilities is unclear, with much evidence suggesting a causal role but other evidence calling this into question (see Puts, et al, 2008), hence the lightly shaded arrows connecting biological sex, brain development, and abilities. While not dismissing the possible causal role of biological factors in sex differences in STEM careers, we find it worth noting that in the past, biological hypotheses have often been believed out of proportion to the evidence supporting them (see Section 12 in the supplemental materials for examples).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the link between biological sex and abilities ( Figure A2 in the supplemental materials), also mediated by an effect on brain functioning and development, findings such as sex differences in white-gray matter ratios are promising but have not been causally linked to male advantage in three-dimensional mental rotation, thought to underlie male superiority in advanced mathematics. Similarly, the relationship between testosterone and spatial abilities is unclear, with much evidence suggesting a causal role but other evidence calling this into question (see Puts, et al, 2008), hence the lightly shaded arrows connecting biological sex, brain development, and abilities. While not dismissing the possible causal role of biological factors in sex differences in STEM careers, we find it worth noting that in the past, biological hypotheses have often been believed out of proportion to the evidence supporting them (see Section 12 in the supplemental materials for examples).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Furthermore, the results have often been quite nuanced in terms of the changes that result from shifting measures, such as spatial targeting with darts versus balls (e.g., Hines et al, 2003) or observations that the relationship between testosterone and spatial cognition is much stronger for males than females only for some measures and at certain times (Davison & Susman, 2001; see Section 3 in the supplemental materials for emblematic inconsistencies). Another example of ambiguity occurs around the question of why the relationship between CAH and spatial ability has been moderately strong in meta-analyses, whereas the relationship between the 2D:4D ratio and spatial ability has not, suggesting that perhaps the critical period for androgens to affect brain regions that subserve spatial ability is later than the first trimester when the 2D:4D ratio occurs (Malas, Dogan, Hilal Evcil, & Desdicioglu, 2006), inasmuch as the CAH effects occur in the later part of pregnancy or even postnatally (Puts et al, 2008). Finally, if elevated prenatal androgens are responsible for spatial ability differences between CAH and non-CAH individuals, this is complicated by the fact that CAH individuals also differ in glucocorticoid levels, which could influence spatial cognition.…”
Section: Biological Sexmentioning
confidence: 99%
“…Although some studies suggested that the sex difference is largely due to different speed-accuracy trade-offs, with females responding more slowly but more accurately than males [71], a meta-analysis with participants between 8 and 29 years of age showed that sex differences are smaller and yet not eliminated by unspeeded conditions [72]. Some researchers have proposed biological reasons for the male advantage, based on findings that exposure to heightened levels of prenatal androgens due to congenital adrenal hyperplasia [73] or male twins [74] were associated with higher MR performance in females.…”
Section: Box 2 Sex Differencesmentioning
confidence: 99%
“…3,[7][8] Androgen plays a role on hippocampus cell formation and development during prenatal period. 6 Unfairly, androgen effect wismore prominent in the right hemisphere development. 4 It is also known that normal androgen level is higher on male than female.…”
Section: -11mentioning
confidence: 99%
“…[3][4][5][6][7][8][9] These differences are still contradiction. Several studies had reported differences and other studies had reported no differences at all.…”
Section: Introductionmentioning
confidence: 99%